Soil chemical factors contributing to differences in bacterial communities among tea field soils and their relationships with tea quality - Zhang, Shuning; Yanagisawa, Naoki; Asahina, Mio; Yamashita, Hiroto; Ikka, Takashi (Frontiers in Plant Science, 2025)
IntroductionSoil chemical properties and bacterial communities play key roles in shaping tea plant nutrient status and quality. While the relationships between soil bacterial communities and plant nutrient status have been investigated, the specific role by which soil bacterial communities interacted with soil properties to influence tea plant nutrients and quality remained underexplored.MethodsIn this study, different soil types were collected from tea gardens and designated as soil A (pH 3.41), soil B (pH 3.75), soil C (pH 4.16), soil D (pH 4.17) and soil E (pH 5.56) based on the initial soil pH. We conducted pot cultivation of tea plant ‘Yabukita’ to investigate how soil chemical factors affect bacterial communities and their influences on the nutrient status and quality of tea plants, and finally explored the complex relationships between soil bacterial features and tea quality.Results and discussionThe results showed that soil bacterial α-diversity was higher level in soils D and E, with distinct β-diversity patterns separating higher pH soils (D and E) from lower pH soils (A, B, and C). The dominant amplicon sequence variants (ASVs) in soils were Proteobacteria (28.12%), Actinobacteriota (25.65%), Firmicutes (9.99%) at phylum level, and Acidothermaceae (7.24%), Solirubrobacteraceae (4.85%), and Acetobacteraceae (4.50%) at family level. Soil pH, exchangeable Mg2+, and Ca2+ were identified as key factors shaping bacterial community composition and positively correlated with bacterial diversity. Differentially abundant ASVs (DAAs) among all soils were also identified including the phylum Firmicutes and families such as Paenibacillaceae, Alicyclobacillaceae, JG36-TzT-191, KF-JG30-C25, and Acidobacteriaceae_subgroup1. Besides, the nutrient content of tea new leaves varied significantly among soil types and harvests. Combined with Mantel-test association analysis, soil chemical properties and soil bacterial communities were jointly correlated with the contents of total nitrogen, potassium, calcium, aluminum, magnesium, free amino acids, and caffeine in tea new leaves. These findings highlight the dynamic interactions between soil properties, bacterial communities, and tea nutrients, emphasizing the importance of optimizing soil health and bacterial networks to improve tea quality.